2014
DOI: 10.2478/s13382-014-0282-8
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and correlates of physical activity among middle-aged employees: A population-based, cross-sectional study

Abstract: Objectives: The purpose of this study was to determine the level, pattern and correlates (socio-demographic, lifestyle and work-related) of physical activity among middle-aged employees in Croatia. Material and Methods: In this cross-sectional study the data were collected using a household interview on a random sample of 766 middle-aged employees (52% female) living in Croatia. The International Physical Activity Questionnaire (IPAQ-long) was used to assess physical activity. An additional questionnaire was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 31 publications
(32 reference statements)
8
10
0
Order By: Relevance
“…Although the cross-sectional correlates of WPA were consistent across surveys, most associations disappeared in the longitudinal analyses, which calls for further longitudinal studies on correlates of WPA. Few studies have examined correlates of WPA, and education is the only variable in previous studies that is consistently correlated with WPA [22, 3133], showing an inverse relation to WPA in accordance with this study. One study showed that age was inversely correlated with WPA [22], similar to our findings, whereas other studies did not find any correlation between age and WPA [31, 33].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Although the cross-sectional correlates of WPA were consistent across surveys, most associations disappeared in the longitudinal analyses, which calls for further longitudinal studies on correlates of WPA. Few studies have examined correlates of WPA, and education is the only variable in previous studies that is consistently correlated with WPA [22, 3133], showing an inverse relation to WPA in accordance with this study. One study showed that age was inversely correlated with WPA [22], similar to our findings, whereas other studies did not find any correlation between age and WPA [31, 33].…”
Section: Discussionsupporting
confidence: 89%
“…Few studies have examined correlates of WPA, and education is the only variable in previous studies that is consistently correlated with WPA [22, 3133], showing an inverse relation to WPA in accordance with this study. One study showed that age was inversely correlated with WPA [22], similar to our findings, whereas other studies did not find any correlation between age and WPA [31, 33]. Previous studies did not find any associations between sex and WPA [22, 31, 33], in contrast to our study; however, our findings disclosed that the association with sex shifted over time.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, level of education and recall bias affect the calculated physical activity level and total energy expenditure of subjective methods. This idea is supported by Jurakic et al [25]. Because our participants had a higher (at least a bachelor degree) education and 9170±2377 steps/day, respectively.…”
Section: Discussionsupporting
confidence: 73%
“…Physical activity is a complex behavior, and every domain of life (work, transport, domestic and garden, and leisuretime) should be researched separately [25]. In addition, accurate and proper assessment of occupational physical activity is an important but challenging task for health and 2084±197 kcal/day, respectively), but the relationship was weak (r = 0.394, p = 0.005).…”
Section: Discussionmentioning
confidence: 99%